2020
DOI: 10.1093/tbm/ibaa086
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of physical activity maintenance during the Covid-19 pandemic: a focus on fitness apps

Abstract: There are various health benefits of regular physical activity (PA) and health risks of sedentariness. The Covid-19 pandemic may have decreased PA and increased sedentariness for several reasons (e.g., closure of gyms, family-related time constraints, and reduced outdoor mobility). Yet, to date, there are no longitudinal studies that examined whether the pandemic affects PA levels and what factors help people remain physically active during lockdown. This study aims to investigate changes in U.S. residents’ PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
87
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 42 publications
13
87
1
5
Order By: Relevance
“…Furthermore, wearables including a daily step counter seemed to be of great use for the determination of individual activity goals. This is in accordance with a recently published study which stated that the use of smartphone apps can improve PA in individuals during a lockdown [17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, wearables including a daily step counter seemed to be of great use for the determination of individual activity goals. This is in accordance with a recently published study which stated that the use of smartphone apps can improve PA in individuals during a lockdown [17].…”
Section: Discussionsupporting
confidence: 93%
“…As stated previously by others, PA was significantly influenced by COVID-19 pandemic associated lockdown measures [14][15][16][17][18]. The multidisciplinary, multimodal, and telemedicine-based KTx360 • program approach might have led to the observed stabilization and even an increase in PA in the KTx360 • participants during the lockdown.…”
Section: Discussionsupporting
confidence: 51%
“…Digital based PA yielded favourable results during the first COVID-19 lockdown, with studies showing positive associations with such digital based initiatives and overall PA during a lockdown. 83 Another finding of this review was that participants who had medical conditions also yielded decreases in PA levels, except for patients with an eating disorder. The decreases in PA is particularly concerning as in several of the medical conditions studied because PA can be a form of treatment or symptom alleviation.…”
Section: Discussionmentioning
confidence: 82%
“…The number of minutes per day spent on physical activity decreased by 33.5% while sitting time increased by 5-8 hours among the respondents 47 . Diminished physical activity levels were also reported in other countries, such as Australia 48 , United Kingdom (UK) 49 , and the United States (US) 50,51 . Longitudinal tracking of steps among participants in a physical activity program in Australia saw a decrease in the number of steps during lockdown, which returned to normal with the lifting of restrictions 52 .…”
Section: Physical Activitymentioning
confidence: 89%
“…There is no predictable pattern as to who was less active during the lockdown period. While some studies found that previously physically active individuals became less active during the lockdown period 51,54 , other studies found no change 50 or reported a further reduction in physical activity among previously inactive individuals 54 . A cross-sectional study in 64 cities in China, with 369 participants, concluded that previously physically active individuals were in greater distress as a consequence of the lockdown 55 .…”
Section: Physical Activitymentioning
confidence: 98%